Influence of Optional Crystallization Firing on the Adhesion of Zirconia-Reinforced Lithium Silicate before and after Aging - Rodrigues, Murilo Rocha [UNESP]; Grangeiro, Manassés Tercio Vieira [UNESP]; Rossi, Natalia Rivoli [UNESP]; de Carvalho Ramos, Nathalia [UNESP]; de Carvalho, Rodrigo Furtado; Kimpara, Estevão Tomomitsu [UNESP]; Tribst, João Paulo Mendes; de Arruda Paes Junior, Tarcisio José [UNESP] (MDPI, 2022)
This study proposed to evaluate the influence of the crystallization firing process and the hydrothermal degradation on the bond strength between different reinforced glass-ceramics and resin cement. Material and Methods: zirconia-reinforced lithium silicate (ZLS) and lithium disilicate (LD) were divided into six groups according to aging simulation (baseline or after thermocycling) and restorative approach (ZLS without firing; ZLS with firing; LD with firing). ZLS and LD surfaces were etched with 5% hydrofluoric acid for 30 s and 20 s, respectively, and then received a layer of silane coupling agent (Monobond-N). Then, cylinders of resin cement (1 mm diameter × 2 mm height) were bonded onto their surfaces. The baseline samples were immersed in distilled water for 24 h before the microshear bond strength (µSBS) test, while half of the specimens were tested after 6000 cycles of thermocycling aging. The types of failures were analyzed through stereomicroscopic and scanning electron microscope. The failure modes were classified as adhesive, predominantly adhesive, cohesive in ceramic, or cohesive in cement. The µSBS data were analyzed by two-way ANOVA and Tukey’s test. A restorative approach (p = 0.000) and aging (p = 0.000) affected the bond strength. The highest bond-strength values were observed in the ZLS without the optional crystallization firing. The most frequent failures were adhesive and predominantly adhesive. The cementation of zirconia-reinforced lithium silicate without the optional crystallization firing process leads to high bond-strength values with resin cement.
Keywords: bond strength; glass-ceramics; lithium silicate; zirconium dioxide